Antenna Tracker System for Unmanned Aerial Vehicles: A Short Review - Hayyan Yusuf; Faisal Rahutomo; Sutrisno Sutrisno (Journal of Electrical, Electronic, Information, and Communication Technology, 2023)
Unmanned Aerial Vehicle (UAV) is a modern technology used to perform difficult and dangerous aerial missions that cannot be carried out by manned aerial vehicles. Ground Control Station (GCS) is a system that manages all the parameters of the UAV. GCS and UAV communicate using radio waves through telemetry, which functions to transmit and receive flight data.  Antenna tracker is a device used to connect the GCS (Ground Control Station) and the UAV (Unmanned Aerial Vehicle). The antenna tracker works by performing tracking to direct the antenna towards the UAV. Nowadays, there are various forms of antennas used in telecommunication technology. Each type of antenna has its own radiation characteristics, some are directional, while others are more omnidirectional. Directional antennas are the right choice to be used with an antenna tracker. Generally, directional antennas have a narrow radiation range but a relatively long transmission distance. This paper provides a review of the state-of-the-art in antenna tracker technology for unmanned aerial vehicles (UAVs), with a focus on design, performance, and type of antenna. The study involved a literature search of various databases. The design approaches for antenna tracker systems range from simple single-axis trackers to sophisticated dual-axis trackers with pan-tilt mechanisms, and type of antenna such as helical were explored. The study concludes that antenna trackers have numerous applications in various industries, including military, agriculture, and surveying, and the demand for reliable and accurate antenna trackers is expected to continue to grow with the increasing popularity of UAVs.